Preparation of 1-Azido-2-Bromo-1,1,2,2-Tetrafluoroethane and Its Use in the Synthesis of N-Fluoroalkylated Nitrogen Heterocycles - Tichý, David; Košt Ál, Vojtěch; Motornov, Vladimir; Klimánková, Iveta; Beier, Petr (The Journal of organic chemistry, 2020)
A straightforward synthesis of 1-azido-2-bromo-1,1,2,2-tetrafluoroethane on a multigram scale from 1,2-dibromotetrafluoroethane and sodium azide in a novel process initiated by organomagnesium compounds (i-PrMgCl·LiCl, turbo Grignard) is reported. Synthetic utility of the title azide in the preparation of N-tetrafluoroethylated and N-difluoromethylated five-membered nitrogen heterocycles was demonstrated with azide-alkyne cycloaddition to N-bromotetrafluoroethyl 1,2,3-triazoles, subsequent reduction to N-tetrafluoroethyl triazoles, rhodium-catalyzed transannulation with nitriles to N-tetrafluoroethylated imidazoles and rhodium-catalyzed ring-opening, and cyclization to N-difluoromethylated oxazoles and thiazoles.